Mechanical, Optical, and Barrier Characteristics of Tapioca and Rice Starch-Based Edible Thermoplastic Antimicrobial Packaging Films - Cokkuvvetli, Ayse Tugce; Yolacan, Oznur; Deniz, Sennur (AMER INST PHYSICS, 2024)
In this study, tapioca and rice starch-based edible antimicrobial packaging films are produced using solvent casting method. The experimental results are optimized using Box Behnken response surface methodology in accordance with the experimental variables (temperature, time, and plasticizer ratio (PR)). Tapioca and rice starch films obtained using milk protein and kappa carrageenan as co-biopolymers on a 25% starch basis were plasticized in the presence of sorbitol. Mechanically optimum starch-based bio-composite film formation parameters are found to be 65 degrees C, 40% PR and 75 degrees C, 45, 40% PR for tapioca and rice starch, respectively. The mechanical strength of rice starch-based films is superior to tapioca starch under optimum experimental conditions. Rice starch-based films have the opposite optical characteristics as tapioca starch-based films, which are brighter and less hazy. Lignin grades as a reinforcing agent have an adverse effect on the transparency of the bio-composite films and does not improve the mechanical strength of the films as anticipating. Melting points and bond structures of starch-based bio-composite packaging films are investigated by FTIR and DSC characterization tests. The obtained tapioca/starch films are found to have adequate mechanical, optical, and barrier qualities for edible packaging films considering the literature. The synergistic effect of poly-lysine and nisin on tapioca starch-based bio-composite films is limited to S. aureus, whereas a synergistic effect on rice starch is only observed for E. coli.
Keywords: Physics; Polymer Science